Salivary Interleukin 6 and Sialic acid in Periodontitis - Jwan Ibrahim Jawzali (Universidade Estadual de Campinas, 2018)
Aim: Periodontitis is the major multi -factorial chronic infectious oral diseases in dentate people. Sialic acid regulates innate immunity response that release cytokines. The study aimed to evaluate interleukin-6 levels in periodontittsis and its relation to clinical features, total sialic acid and its fraction and total proteins to clarify its role. Material and Methods: The study was observational case-control study, carried out in periodontology clinic, College of Dentistry / Erbil /Iraq. A total of 60 participants were recruited in this study, They were divided into three groups: control group represent systemically and periodontally healthy subjects, clinically, diagnosed dentate periodontitis group and partial edentulous group.The data was collected through interview questionnaire, clinical periodontal examination, and biochemical tests for salivary; IL-6.total sialic acid and its fraction, and salivary total proteins Statistical analysis was done by statistical Package for Social Sciences. Results: Statistical analysis showed a significant (P≤ 0.01) highest value of total sialic acid in periodontitis. While the highest value of IL-6 was in partial edentulous group. Old ages increased salivary IL-6 significantly. In periodontitis there was significantly association of IL-6 with probe pocket depth, mobility scores of teeth, protein bonund sialic acid and significant negative association with lipid bound sialic acid in precipitate. While in partial edentulous IL-6 associated significantly with gingival index and free sialic acid in precipitate and negatively with probe pocket depth. Conclusions: Salivary sialic acid and IL-6 are periodontitis biomarkers in dentate. Pleiotropic role of IL-6 can be diagnosed by sialic acid levels. It depends on age, (which affects number of teeth and salivary flow rate), and treatment conditions.